Emodin mitigates rheumatoid arthritis through direct binding to TNF-α - Lu, Dingyan; Tian, Xudong; Cao, Taotao; Chen, Shuaishuai; Liu, Chunhua; Zheng, Lin; Zhou, Meng; Peng, Xiaoyan; Li, Yongjun; Liu, Ting (Frontiers in Pharmacology, 2025)
Emodin has shown certain anti-rheumatoid arthritis (RA) activity in preliminary studies. However, the precise mechanisms of emodin’s anti-RA effects, particularly its direct targets, remain unclear. This study aimed to evaluate the anti-RA activity of emodin and elucidate its potential mechanisms, with a specific focus on identifying its molecular targets. Employing a collagen-induced arthritis (CIA) rat model, along with transcriptomic analysis, thermal proteome profiling (TPP) and TNF-α-induced L929 cell model, the anti-RA activity of emodin was confirmed, identifying TNF-α as a potential target. Techniques such as drug affinity responsive target stability (DARTS), cellular thermal shift assay (CETSA), Affinity ultrafiltration-liquid chromatography/mass spectrometry (AUF-LC/MS), surface plasmon resonance (SPR) and bio-layer interferometry (BLI) validated the direct binding of emodin to TNF-α. Molecular dynamics simulation, ELISA and BLI further revealed that emodin stabilizes the asymmetric trimeric structure of TNF-α, disrupting the TNF-α-TNFR1 interaction. In vitro assays, including luciferase reporter gene assay and TNF-α-induced MH7A cell model, demonstrated that this disruption inhibits TNF-α-induced NF-κB activation, leading to the downregulation of inflammatory mediators such as IL-6, IL-1β, and COX2. In conclusion, emodin directly targets TNF-α, stabilizing its structure and blocking TNF-α-TNFR1 interaction, which subsequently suppresses downstream NF-κB pathway activation and contributes to its potent anti-RA properties.